Podocyte injury in diabetes mellitus - Irina Nikolaevna Bobkova; Marina Vladimirovna Shestakova; Anna Alexandrovna Shchukina (Сахарный диабет)
The mechanisms of podocyte injury and their correlation with metabolic and haemodynamic disorders in diabetes mellitus are considered in detail; the results of the last experimental and clinical studies on this problem are presented in this review. Authors shined the biomarkers, reflecting expressiveness of podocytopathy and structural and functional glomerular changes at diabetic nephropathy. Modern possibilities of treatment for their correction to prevent diabetic nephropathy progression are discussed.